'Relationship between thermal dose and cell death for "rapid" ablative and "slow" hyperthermic heating'. (1st January 2019) - Mouratidis, Petros X. E.; Rivens, Ian; Civale, John; Symonds-Tayler, Richard; ter Haar, Gail
Abstract: Aim: Thermal isoeffective dose (TID) has not been convincingly validated for application to predict biological effects from rapid thermal ablation (e.g., using >55 °C). This study compares the classical method of quantifying TID (derived from hyperthermia data) with a temperature-adjusted method based on the Arrhenius model for predicting cell survival in vitro, after either 'rapid' ablative or 'slow' hyperthermic exposures. Methods: MTT assay viability data was obtained from two human colon cancer cell lines, (HCT116, HT29), subjected to a range of TIDs (120–720 CEM43 ) using a thermal cycler for hyperthermic (>2 minutes, <50 °C) treatments, or a novel pre-heated water bath based technique for ablative exposures (<10 seconds, >55 °C). TID was initially estimated using a constant RCEM>43 °C =0.5, and subsequently using RCEM (T), derived from temperature dependent cell survival (injury rate) Arrhenius analysis. Results: 'Slow' and 'rapid' exposures resulted in cell survival and significant regrowth (both cell lines) 10 days post-treatment for 240 CEM43 (RCEM>43 °C =0.5), while 340-550 CEM43 (RCEM>43 °C =0.5) delivered using 'rapid' exposures showed 12 ± 6% viability and 'slow' exposures resulted in undetectable viability. Arrhenius analysis of experimental data (activation energy ΔE = 5.78 ± 0.04 × 10 5  J mole −1, frequency factor A  = 3.27 ± 11 × 10 91  sec −1 ) yielded RCEM =0.42 * e 0.0041*T which better-predicted cell survival than using R CEM> 43 °C =0.5. Conclusions: TID calculated using an RCEM (T) informed by Arrhenius kinetic parameters provided a more consistent, heating strategy independent, predictor of cell viability, improving dosimetry of ablative thermal exposures. Cell viability was only undetectable above 305 ± 10 CEM43 using this revised measure.